HUBUNGAN MODAL SOSIAL TERHADAP KEBERLANJUTAN USAHA NELAYAN DI DESA LAMBANGI KECAMATAN KOLONO TIMUR KABUPATEN KONAWE SELATAN - Yani Taufik; Salahuddin Salahuddin (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This research aims to (1) determine the social capital of fishermen in Lambangi Village, East Kolono District, South Konawe Regency; (2) knowing the business sustainability of fishermen in Lambangi Village, East Kolono District, South Konawe Regency; and (3) determine the relationship between social capital and business sustainability among fishermen in Lambangi Village, East Kolono District, South Konawe Regency. The data analysis used in this research is the class interval formula and spearman rank correlation with the help of SPSS 25. The results of the research show that the elements of social capital of fishermen in Lambangi Village consist of trust, participation and networking and the results of the research show that the application of trust is categorized as high; implementation of participation is categorized as good; and network implementation is categorized as sufficient. The level of sustainability of fishing businesses in Lambangi Village, East Kolono District, South Konawe Regency based on its category is categorized as medium. And there is a relationship between social capital, namely trust, participation and networks, to the sustainability of fishing businesses. Based on the calculation results, it shows that the Spearman rank correlation test results have a correlation coefficient of 0.604 with a significance level of 0.000. This shows that social capital and the sustainability of fishing businesses have a close relationship based on a coefficient value of 0.604 which is seen based on the degree of relationship guidelines. And it can also be a significant or sig value. (2-tailed) 0.001< or smaller than 0.05 then it can be said to be significant.